New digital technologiesas a new boost modelcompetence of parents in matters of upbringing and education - Analbekova, K.T. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The article provides an overview of modern approaches to understanding the process of digitalization, gives the possibility of their use in the educational process of a preschool educational organization.
Жаңа цифрлық технологиялар жаңа күшейту үлгісі ретінде ата-аналардың тәрбие мен білім беру мәселелеріндегі құзыреті
Новые цифровые технологии как новая модель повышения компетентности родителей в вопросах воспитания и образования
Keywords: digital educational environment; information and communication technologies; preschool educational organization; digital technologies